Young Lives School Surveys 2016–17: Vietnam country report - Iyer, P; Rolleston, C; Azubuike, B (Young Lives, 2017)
This report provides an overview of the Young Lives secondary school survey in Vietnam, which was conducted in 2016-17 with 8,740 Grade 10 students in five provinces (Ben Tre, Da Nang, Hung Yen, Lao Cai and Phu Yen). The survey was designed to allow analysis of the factors that shape students’ learning and progression over one academic year, and descriptive analyses of the survey data are presented in this report. The secondary school survey examined school effectiveness using three outcome measures: Grade 10 students’ performance in maths, functional English, and transferable skills. Student performance in maths and functional English was assessed using repeated measures, with linked cognitive tests administered at the beginning and end of Grade 10. This allowed students’ progress over the first year of upper secondary schooling to be considered in relation to their individual, class, teacher and school factors. Students’ problem-solving and critical-thinking skills were additionally assessed at the end of the school year using the transferable skills test. This survey design has generated rich evidence about school and class effectiveness, and the drivers of learning within schools across the Young Lives sites in Vietnam.